Effects of Thymoquinone on Hypothalamic NPY and AgRP Gene Expression in Intact and Hypothyroidism- Model Rats - Nasrin Ghahremani; Fariba Mahmoudi (Fasa University of Medical Sciences, 2022)
Background & Objective: Thymoquinone is the most important compound of Nigella sativa, which stimulates the activity of thyroid axis in healthy individuals and people with hypothyroidism. The present study investigated the effects of thymoquinone on Neuropeptide Y (NPY) and Agouti-dependent peptide (AgRP) gene expression in the hypothalamus of healthy individuals and hypothyroidism- model rats Material & Methods: Twenty male Wistar rats weighing 190- 220g were used. Hypothyroidism was induced by a daily consumption of Methimazole (20mg/kg) for 42 days via drinking water. Control rats received the intraperitoneal injections of saline. Intact or hypothyroid rats received the intraperitoneal injections of thymoquinone (10mg/kg) for 15 days. One day after last injection, the thyroid gland and hypothalamic samples were dissected. Thyroid gland samples were used for histological study. Relative gene expression of hypothalamic NPY and AgRP was determined by real-time polymerase chain reaction. Results: Thymoquinone significantly declined the NPY and AgRP gene expressions in the hypothalamus of intact rats in comparison with control group. Induction of hypothyroidism results in a remarkable increase in the NPY and AgRP gene expressions compared to control rats. In hypothyroid rats receiving thymoquinone, the mean relative NPY and AgRP gene expressions showed an insignificant decrease compared to hypothyroid group. Conclusion: Because AgRP/NPY signaling pathway exerts inhibitory effects on thyroid gland function, thymoquinone may stimulate thyroid axis activity partly via inhibiting the hypothalamic AgRP/NPY gene expression in intact rats. In hypothyroidism, used dose of thymoquinone may not able to cause a significant decrease in AgRP/NPY gene expression due to its increased levels.